Legal responsibility for the utilization of artificial intelligence that has occurred system error from the perspective of criminal law - Fransisco, Wawan; Hafrida, Hafrida; Kusniati, Retno (Institute Of computer Science (IOCS), 2025)
Every advancement in artificial intelligence and every application built on it must be accompanied by considerations of law, ethics, and humanity. Complex legal issues are inextricably linked to this quick development. The purpose of this study is to determine, examine, and address the legal liability that results from defects in artificial intelligence. Criminal liability is the primary focus of the artificial intelligence issue. The report offers comprehensive insights into recent legal developments, regulatory initiatives, and suggestions to get over these challenges as a result of this investigation. As a result, this study advances knowledge of the legal dynamics surrounding AI legal liability and encourages more conversation in this field.